2015
DOI: 10.5603/piap.2015.0056
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia as a Marker of Outcome in Patients with Acute Exacerbation of Chronic Obstructive Pulmonary Disease

Abstract: Introduction: Thrombocytopenia (TP) is associated with poor outcome in patients who are critically ill with pneumonia, burns, and H1N1 influenza. To our knowledge, no similar study in patients with acute exacerbation of chronic obstructive pulmonary disease (AECOPD) has been conducted to date. The aim of this study was to determine the impact of platelet count on the outcome of patients with AECOPD. Material and methods: Patients admitted to our teaching hospital for AECOPD were divided into two cohorts, those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 24 publications
6
29
1
Order By: Relevance
“…42 Clinically, eosinopenia has been suggested to be a prognostic marker for critically ill patients admitted to the Intensive Care Unit and those with COPD AE. [43][44][45] Both higher GPS and eosinopenia are representative of acute inflammation, and these factors were related with poor clinical outcomes in patients with IPF-AE in our study. Based on this finding, we suggest that inflammatory exacerbations of IPF are related to poor clinical outcomes.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…42 Clinically, eosinopenia has been suggested to be a prognostic marker for critically ill patients admitted to the Intensive Care Unit and those with COPD AE. [43][44][45] Both higher GPS and eosinopenia are representative of acute inflammation, and these factors were related with poor clinical outcomes in patients with IPF-AE in our study. Based on this finding, we suggest that inflammatory exacerbations of IPF are related to poor clinical outcomes.…”
Section: Discussionsupporting
confidence: 50%
“…During the acute stage of inflammation, rapid peripheral sequestration and migration of circulating eosinophils to the site of infection by cytokines and chemotactic substances results in eosinopenia . Clinically, eosinopenia has been suggested to be a prognostic marker for critically ill patients admitted to the Intensive Care Unit and those with COPD AE . Both higher GPS and eosinopenia are representative of acute inflammation, and these factors were related with poor clinical outcomes in patients with IPF‐AE in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Platelets play an important role in inflammation. Thrombocytopenia is associated with poor outcome in AECOPD and several other diseases (31)(32)(33)(34)(35). Association of lymphopenia with mortality has already shown in sepsis, in critically ill emergency general surgical patients, and heart failure (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…22 However, the effect of blood eosinophil in AECOPD outcomes remains controversial. Two studies found longer hospitalization, 23,24 a greater need for mechanical ventilation, 23 and increased mortality 23,24 in the group with eosinophilia. Further, a higher frequency of readmission for AECOPD 25 and a higher rate of exacerbations 26 have been found in those with eosinophilia.…”
Section: Introductionmentioning
confidence: 98%